PENGEMBANGANPAKET PELATIHAN PERILAKU ASERTIFDALAM HUBUNGANTEMAN SEBAYA SISWA KELAS VIII DI SMP NEGERI 9 MALANG - Langensari Diorani (LP2M IAI Al Khairat Pamekasan, 2020)
Abstract : The general objective in the development of this research is to produce a training packet assertive behavior in peer relationships of eighth grade students in SMPN 9 Malang, which can help counselors to provide guidance and counseling services concerning assertive behavior effectively so that students can demonstrate assertive behavior in relation to negative influences friends of the same age. The specific objective of this research is that it can produce training packet assertive behavior has accuracy, usability, convenience and attractiveness so that it can improve assertive behavior of junior high school students.This study uses a design research and development by adapting models Borg and Gall (1983), which consists of several stages, among others: (1) data collection; (2) planning; (3) developing initial products; (4) the initial product trials; (5) a revision of products based on suggestions from the field test results; (6) conduct field trials is limited; and (7) to revise the final product.Based on the results of the development, training packet assertive behavior in junior high school students peer relationships can be concluded that the training packet assertive behavior in peer relationships junior high school students theoretically and practically acceptable from the aspect of accuracy, usability, convenience, and attractiveness.The results of the study suggested that counselors should understand and learn the steps of training and training materials in the packet before applying to the students. For further research, product research and development can be followed by experimental studies to determine the effectiveness of the training packet assertive behavior in peer relationship. Keywords : Assertiveness training, Peer relationships